KANDUNGAN SERATKASAR Centrosema pubescens DAN Capologonium mucunoides DI KAMPUNG WASUR - Yenni Pasaribu; Irine Ike Praptiwi (Universitas Musamus, Merauke, Papua, 2014)
The aim of this research was to know the chemical composition especially the crude fiberof Centrocema pubescensand Calopogonium mucunoides that grow in Wasur area as ruminant feed. The research was conducted in Wasur Village, Merauke regency and the proximate analysis was conducted in the Biologi Hewan laboratory of PAU Bogor Agricultural University.Sample used in this research werefeeding grass of leguminose which grow around Wasur area. The results showed that the crude fiber content inC. pubescensand C. mucunoides was 17,59 and 19,36%, respectively.